“Glorious uncertainty”: Business and Adultery in Charlotte Riddell’s Too Much Alone - Colella, Silvana (Romanticism and Victorianism on the Net, 2011)
In the 1860s and 1870s Charlotte Riddell was well-known as the “novelist of the City” of London. Too Much Alone (1860), her first narrative foray into the world of commerce and finance, is both a business novel and a novel of adultery. Focusing on how the text configures the emotional regimes of capitalism, this essay examines Riddell’s representation of irregular desires and capricious feelings in relation to what she sees as endemic in commercial society: not fraud, but insecurity and uncertainty, whether “glorious” or dreary. The experience of uncertainty, I argue, provides the point of intersection between the two narrative strands of business and adultery. Explicitly addressed to business people, the novel offers a lesson in sentimental education, a type of training in the ability to tolerate the uncertain, repackaged as an intense emotional experience.